MECHANICAL PROPERTIES IMPROVEMENT OF FIBER REINFORCED CONCRETE - Jan Trejbal; Václav Nežerka; Radim Hlůžek; Zdeněk Prošek (Acta Polytechnica CTU Proceedings)
Fiber reinforced concrete mechanical properties are limited due to low adhesion between polymer fibers and cement matrix. To ensure a strong interaction between the two materials, polypropylene fibers (d = 0.305mm) were modified by an oxygen plasma treatment. The interface interaction was moreover activated using finely ground concrete recyclate, whose individual grains (1−64 μm) ensure an adhesion improvement in interfacial zones. The adhesion enhancement was verified by pull-out tests, when reference and modified fibers were pulled-out from cement matrix specimens. Such obtained results were used as a crucial parameter to numerical simulations of bending tests of specimens (550 × 150 × 150mm) with properties following fiber reinforced concrete. It was shown that samples reinforced with modified fibers and contained activating recyclate reached on higher residual bending strength then those with reference fibers.